Electromyographic study of rotator cuff muscle activity during full and empty can tests - Kai, Yoshihiro (Asia Pac J Sports Med Arthrosc Rehabil Technol, 2015)
The empty can (EC) and full can (FC) tests are used as diagnostic tools for patients with rotator cuff disease. However, recently concerns have been raised that these tests do not selectively activate the muscle. Therefore, the purpose of this study was to evaluate the rotator cuff muscle activation levels during the EC and FC tests in various positions using electromyography. Twelve healthy, right-handed men without shoulder complaints (mean age: 26.1 years, range: 23–35 years) were included. The tests were performed isometrically with the shoulder elevated at 45° and 90° in the sagittal, scapular, and coronal planes, either in the thumb-up (FC test) or thumb-down (EC test) positions. During these positions, the electromyographic signal was recorded simultaneously from the four shoulder muscles using a combination of surface and intramuscular fine-wire electrodes. The average activation of the supraspinatus and subscapularis was greater during the EC test than during the FC test and in the scapular and coronal planes than in the sagittal plane at 90°. For the infraspinatus, there were no significant differences in any positions between the two tests. Thus, the rotator cuff muscles are influenced by arm position and the elevation plane during the EC and FC tests.